Analysis of Abnormal Return of Issuer’s Stock after IPO during the Covid-19 Pandemic - I G W Yoga; N W K Dewi; I Made Sumartana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The Covid-19 pandemic based on Presidential Decree Number 12 of 2020 was declaredon April 13, 2020. During this Pandemic, many companies offer their shares to the public or known as Initial Public Offering (IPO). This study aims to find out the highest abnormal returns of the issuers' stock after the IPO during the Covid-19 Pandemic. The sample used in this study was 70 companies that IPO on the IDXafter pandemic status was declared in Indonesia, namely from April 15, 2020-November 25, 2021. This research is a descriptive quantitative research anddescriptive statistical analysis techniques was used to calculate abnormal returns and cumulative abnormal returns of each stock. The results showed that cumulatively, the highest abnormal return of 70 stocks within 20 months was owned by TECH shares in the technology sector with a cumulative abnormal return value of 23,562. Meanwhile, the lowest value is owned by DEPO shares in the consumer cyclicals sector with a cumulative abnormal return of 0.624. The results of this study can be used as considerationby investors who want to invest in IPO stocks during prolonged outbreaks such as the Covid-19 Pandemic.